Labor requirements, irrigated crops 1947: labor requirements for producing sugar beets, potatoes, barley, and beans under irrigation, Weld County, 1947 - Shaw, Kenneth McKendree, author; Burdick, R. T. (Raymond Terry), 1889-1982, advisor; Romine, Dale Servetus, committee member; Creek, C. Richard, committee member; Paschal, J. L. (James Leo), 1906-, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Farm management; Sugar growing -- Colorado; Agriculture -- Colorado -- Weld County; Agriculture -- Economic aspects